Problems of legal understanding in the modern philosophy of law (Journal of actual problems of jurisprudence, 2018)
The paper is aimed to explore the issues of legal understanding in the modern philosophy of law. The history of law and legal thought is saturated with struggle of two legal understanding types: law and legist. It is noted that the legal understanding type is influenced by political (class), historic, ideological and epistemological reasons, political partiality and class interests, special legal studies. In conclusion it is said about the absence of the general classification of legal understanding types, existence of the two most important principles of post-industrial science: verification and falsification. Tendencies of modern legal understanding are outlined. Peculiarities of meta law and its levels and views are reflected in the present paper.Key words: legal understanding, Law science, philosophy of law, theory of la, legal understanding type, postmodern, meta law.